Behaving badly : psychiatric and sociological perspectives on young people with 'conduct disorder' - Harvey, Dominique (2006)
Background: Despite its status within internationally agreed psychiatric systems, the extent to which the behavioural symptoms of Conduct Disorder are indicative of mental disorder is debatable. The aim of this thesis is to assess the extent to which the collection of behaviours currently defined as Conduct Disorder might be better understood within a sociological framework. Methods: In-depth semi-structured interviews were carried out to explore young people’s perspectives on behaving badly. Most of the participants interviewed met DSM-IV criteria for Conduct Disorder, which was identified on the basis of Voice-DISC profiles at two earlier phases of the West of Scotland 11-16/16+ study (West, Sweeting, Der et al., 2003). Findings. The findings highlighted that behaving badly was generally perceived as normative, purposive and adaptive, therefore reflecting more sociological interpretations of behaving badly. Two participants appeared to link their behaviour to mental distress, which provided limited support for the view that some forms of antisocial behaviour might be indicative of mental disorder. Since young people often depicted behaving badly as adaptive and purposive, the findings suggested that epidemiological research may be neglecting the positive functions of antisocial behaviour for young people. Implications. An in-depth exploration of young people’s accounts led to the conclusion that the current diagnostic criteria for Conduct Disorder are over-inclusive. Four amendments to the criteria were proposed which might help to distinguish between individuals with disorderly conduct and those with Conduct Disorder before the publication of DSM-V and ICD-1